Sustainability and digital engineering management : African case studies in sustainable digital transformation - Telukdarie, Arnesh (Emerald Publishing Limited, 2025)
Sustainability and Digital Engineering Management showcases real-world case studies that demonstrate how digital technologies can help engineering managers achieve sustainable outcomes. The book spans a variety of innovative projects across multiple sectors, emphasising the substantial benefits of integrating sustainability within digital transformation initiatives. Offering practical insights into successful applications across diverse settings, the book presents examples of how to tackle current industry challenges with sustainable solutions. The chapters delve into various themes such as sustainable operations, business practices, urban and rural development, and education and skill development. They also address challenges encountered during implementation and the opportunities that emerged. Together, the case studies provide a detailed look at Africa's rapidly evolving digital landscape and offer valuable methods and techniques for achieving sustainability goals in areas such as water supply, urban planning, rural development, education, healthcare, manufacturing and mining. Sustainability and Digital Engineering Management is a key resource for practitioners, including engineers and project managers, who seek to integrate sustainability principles into engineering projects, as well as students seeking real-world examples of solutions to various sustainability challenges.
Includes index.
Keywords: Engineering.; Technology & Engineering -- Engineering (General); Engineering: general.; elektronické knihy; electronic books